Analisis Dampak Sampah Domestik terhadap Lingkungan Perairan Pesisir dan Kesehatan - Fitri Sadilla; Eni - Kamal; Abdul - Razak; Widya Prarikeslan (Poltekkes Kemenkes Padang, 2025)
Coastal waters are vital ecosystems that support marine life and human activities such as fisheries and tourism. However, population growth and urbanization have led to a surge in domestic waste, particularly plastics and liquid waste containing hazardous chemicals. Poor waste management pollutes coastal ecosystems, degrades the environment, and poses health risks to communities. This study aims to formulate evidence-based recommendations for sustainable waste management to minimize its impact on coastal environmental quality and public health. The method used is a Systematic Literature Review (SLR) based on 15 relevant scientific articles. The findings indicate that domestic waste contributes to eutrophication, water quality deterioration, and microplastic exposure, contaminating the marine food chain. The health effects include respiratory disorders, skin diseases, and gastrointestinal infections. Additionally, inadequate waste management infrastructure and low public awareness exacerbate the problem. Conclusion : Domestic waste has a significant impact on coastal ecosystems and public health. Poorly managed plastic and liquid waste contribute to eutrophication, water quality degradation, and microplastic contamination, which can disrupt the marine food chain.